Cyclopoids feed selectively on free‐living stages of parasites. (15th April 2020) - Mironova, Ekaterina; Gopko, Mikhail; Pasternak, Anna; Mikheev, Viktor; Taskinen, Jouni
Abstract: Many aquatic organisms can consume parasite larvae, thus hampering parasite transmission; however, information about feeding on them in the presence of an alternative prey remains scarce. When having a food choice, predators may decrease parasite consumption, therefore, it is important to assess the role of parasites in the diet of predators in natural communities with different types of prey available. Our study aims to test whether common freshwater cyclopoids feed on trematode free‐living stages (cercariae) when an alternative food source is present. We experimentally studied ingestion rates of cyclopoids Macrocyclops distinctus fed with cercariae of trematode Diplostomum pseudospathaceum, a common and harmful parasite of freshwater fishes, and ciliates Paramecium caudatum (an alternative prey, known as suitable food for copepods). First, the feeding response of cyclopoids to different densities of each prey was studied. Then, feeding selectivity in the mixtures of cercariae and ciliates was tested. Feeding rates of cyclopoids increased with prey densities (both ciliates and cercariae) but almost stopped growing at high prey densities, which indicated saturation (Holling type II functional response). In most cases, cyclopoids consumed cercariae at higher rates than ciliates. Maximum ingestion rates estimated from the obtained curves were 37 cercariae ind −1  hr −1 and 17 ciliate ind −1  hr −1 . When exposed to prey mixtures, cyclopoids fed on cercariae selectively. When cercariae were offered to cyclopoids at concentrations exceeding the saturation level, the ingestion of ciliates remained constantly low at all ciliate densities. In contrast, the ingestion of cercariae increased with rising cercariae densities even when ciliates were presented ad libitum, decreasing only at very high prey densities . Possible reasons of such feeding preferences are discussed. Our study demonstrated that cyclopoids may prefer to feed on cercariae when there is an alternative food choice and can ingest cercariae at high rates. These experimental results could be extended to natural communities, suggesting that cyclopoids can reduce the transmission of parasites and contribute to the incorporation of parasite production in food webs of lentic ecosystems.